Theo the autobiography of Theodore Bikel - Bikel, Theodore 1924-2015 (HarperCollins, 1994)
Theodore Bikel is an activist: from his early involvement with the struggle for civil rights to his support and active campaigning for then-Senator John F. Kennedy, through his work for progressive causes the world over, from Tel Aviv to Tbilisi. And with that voice, the voice that has won him applause as a singer, and, as an actor, an Emmy, an Oscar nomination, and countless other citations for his talent and his commitment
Keywords: Bikel, Theodore; Bikel, Theodore -- 1924-2015; Actors -- United States -- Biography; Jewish actors -- United States -- Biography; Jewish singers -- United States -- Biography; Singers -- United States -- Biography; Autobiografie; USA; Biografie